Transient High-Pressure Hydrogen Jet Measurements - Peterson, Benjamin R. (My University, 2009)
Jets produced by prototype multi-hole gaseous injectors were visualized using schlieren methods. Hydrogen and helium were injected at pressures ranging from 1.3 bar to 104 bar into chamber densities ranging from 1.15 to 12.8 kg/m3, resulting in jets spanning from subsonic to highly underexpanded conditions. The jet tip penetration rate was found to increase with injection pressure, and decrease with increasing chamber density, as expected. The jet angle was also measured, but variability in the results restricted the quantitative assessment of trends. The complex expansion and shock structures within the underexpanded jets were clearly visible, and the distance between the expansion wave fronts was found to scale directly with the ratio of the exit to chamber pressure. Two injector characteristics, the discharge coefficient and rate shape, were measured to describe injector performance. The discharge coefficient was found to range from 0.19 to 0.33, while the rate shape displayed ?top hat? behavior for all conditions tested. Five normalization models that included the effects of expansion outside the nozzle, jet angle variation, and discharge coefficient variation were investigated to analyze their importance in the collapse of the penetration rate data from the three- and seven-hole injectors.. The nondimensional penetration was found to be linearly dependent on the square root of the nondimensional time, indicating self-similar behavior for each investigated normalization scheme. The uncertainty of the slopes of individual runs was quantified and was found to vary for each method, with no clearly superior method.